Which Sounds are Significant? Towards a Rhetoric of Closed Captioning - Sean Zdenek (Disability Studies Quarterly, 2011)
This article offers a way of thinking about closed captioning that goes beyond quality (narrowly defined in current style guides in terms of visual design) to consider captioning as a rhetorical and interpretative practice that warrants further analysis and criticism from scholars in the humanities and social sciences. A rhetorical perspective recasts quality in terms of how genre, audience, context, and purpose shape the captioning act. Drawing on a range of Hollywood movies and television shows, this article addresses a set of topics that are central to an understanding of the effectiveness, significance, and reception of captions: overcaptioning, undercaptioning, subtitles vs. captions, the manipulation of time, non-speech information, series awareness, and the backchannel.
Keywords: Closed captioning; deaf; rhetoric; style; video